Synthesis of Silver-Chitosan Nanocomposites Colloidal by Glucose as Reducing Agent - Endang Susilowati; Triyono Triyono; Sri Juari Santosa; Indriana Kartini (Indonesian Journal of Chemistry, 2015)
Silver-chitosan nanocomposites colloidal was successfully performed by chemical reduction method at room temperature using glucose as reducing agent, sodium hydroxide (NaOH) as accelerator reagent, silver nitrate (AgNO3) as metal precursor and chitosan as stabilizing agent. Compared to other synthetic methods, this work is green and simple. The effect of the amount of NaOH, molar ratio of AgNO3 to glucose and AgNO3 concentration towards Localized Surface Plasmon Resonance (LSPR) absorption band of silver nanoparticles was investigated using UV-Vis spectrophotometer. The stability of the colloid was also studied for the first 16 weeks of storage at ambient temperature. The formation of silver nanoparticles was confirmed by the appearance of LSPR absorption peak at 402.4–414.5 nm. It is also shown that the absorption peak of LSPR were affected by NaOH amount, ratio molar AgNO3/glucose and concentration of AgNO3. The produced silver nanoparticles were spherical with dominant size range of 6 to 18 nm as shown by TEM images. All colloidals were stable without any aggregation for 16 weeks after preparation. The newly prepared silver-chitosan nanocomposites colloidal may have potential for antibacterial applications.